If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3cosx + 9 = 7 Reorder the terms: 9 + 3cosx = 7 Solving 9 + 3cosx = 7 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3cosx = 7 + -9 Combine like terms: 9 + -9 = 0 0 + 3cosx = 7 + -9 3cosx = 7 + -9 Combine like terms: 7 + -9 = -2 3cosx = -2 Divide each side by '3osx'. c = -0.6666666667o-1s-1x-1 Simplifying c = -0.6666666667o-1s-1x-1
| 3r^2+r-16=2r^2-8+8r | | 20.6+2.1x=8.2x | | (X-3i)(x+3i)=y | | 3B-2=5K-3 | | 7(4-2s)-6s=3 | | 56x^2-9x-81= | | L=5w-3 | | 9(a+5.8)+8.2a=5 | | 45a+172= | | 541x=64 | | 64x-541=-803 | | -x^2-9x+3=0 | | 180=13x-8+3x+7x+4 | | 9a^2+12a+7=0 | | ln(x(x-10))=5 | | 541x=803 | | -4d-6=-6d-4 | | 541x-803=64 | | 10-2q=8 | | 3+34+674= | | 30(50x+20)+40=200 | | 8*o=98 | | 5x-4+7x-18=8x+2 | | r/6+r/6=5 | | 2(2x-3)=5x-11 | | -5x^2+250x-130000=5000 | | (x^2)-19x+9.5=0 | | (x+18)=688 | | 0.4(x+7)-0.1(3x+6)=-0.8 | | 17+20-3=17y | | y=6xt+5xt^2+6 | | 15d+3.2=92 |